ANALISIS HUBUNGAN JANGKA PANJANG NASABAH DENGAN BANK SYARIAH (Studi Kasus pada Bank Syariah di Kota Padang-Sumatera Barat) - Yasri Yasri (Jurnal Bisnis dan Ekonomi, 2006)
The objective of this research is is to analyze the long-term relationship between syariah banks in Padang and their customers, so that the structure of direct and indirect of exogenous variables on the relationship between banks and their customers can be formulated. The population of this research is all customers of syariah in Padang West Sumatera.  The sample size comprises 380 sample units, which is selected with proportional cluster random sampling. The analysis technique is path analysis. The research indicates that indirect influences of each exogenous variable bigger than the direct influence. The correlation of each exogenous variable is highly significant. Total influence all of exogenous variables on endogenous ones is 70,60%. Three of six exogenous variables, i.e, commitment, empathy and trust have bigger influences on the  long-term relationship between the banks syariah and their customers. Mean while, the smallest influence is given by equality and dependence.Key words: long-term relationship, commitment, empathy and trust.